MANETSip - A Dependable SIP Overlay Network for MANET Including Presentity Service - Fudickar, Sebastian; Rebensburg, Klaus; Schnor, Bettina (The Fifth International Conference on Networking and Services, 2009)
This work presents a dependable SIP overlay network for the usage in mobile ad hoc wireless networks focusing the availability of registrar and location services in combination with a reduced message transmission overhead regarding amount and size. In addition we enable a SIP presentity service which offers subscriber presentity state information to others. We show the performance of our approach through measurements with a prototype in a testbed.